FACTORS INFLUENCING THE ADOPTION OF SASSAKAWA GLOBAL (SG 2000) TECHNOLOGIES ON MAIZE PRODUCTION IN CENTRAL AGRICULTURAL ZONE OF BAUCHI STATE, NIGERIA - Abdurrahman, A.; Idi, S.; Abdullahi, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the factors influencing the impact of adoption of Sasakawa Global (SG 2000) technologies on maize production in Central Agricultural Zone of Bauchi state. Multi-stage sampling technique was employed in selecting 174 respondents. Data were collected using structured questionnaire and analysed using descriptive and inferential statistics. The study revealed that, farmers demonstrated high adoption rates for core SG 2000 agronomic practices, including planting time (90.8%), weed control (88.5%), spacing (83.9%), pest/disease control (83.9%), single seed per plant (81.6%), and appropriate fertilizer application (79.3%). Adoption of harvest and storage technologies was lower (59.8%). The adoption of these technologies showed a profound positive impact (P<0.01) significantly correlating with increased maize farm size, quantity harvested, sales earnings, and ownership of various assets (e.g., cars, motorcycles, household items), indicating improved livelihoods and wealth. Income (P< 0.01), farm size (P< 0.01), cooperative membership (P< 0.01), household size (P< 0.05) and marital status (P< 0.05), were the factors significantly influencing adoption of the SG 2000. The major constraints to the adoption of the SG 2000 were inadequate credit facilities (0.691), high cost of farm inputs (0.675), and high incidence of pests/diseases (0.737). The study concluded that adoption of SG 2000 had a significant impact on productivity, income and overall welfare of the respondents. Also, adoption of SG 2000 production technologies was influenced by income, farm size, marital status, household size, occupation, farm size and membership of cooperative societies. It was recommended that efforts should be intensified to strengthen existing cooperatives, government and development partners should prioritize investment in improving rural road networks and transportation facilities to reduce post-harvest losses and enhance market access for maize farmers.